A case study on the genetic origin of the high oleic acid trait through FAD2-1 DNA sequence variation in safflower (Carthamus tinctorius L.) - Rapson, Sara; Wu, Man; Okada, Shoko; Das, Alpana; Shrestha, Pushkar; Zhou, Xue-Rong; Wood, Craig; Green, Allan; Singh, Surinder; Liu, Qing (Frontiers in Plant Science, 2015)
The safflower (Carthamus tinctorius L.) is considered a strongly domesticated species with a long history of cultivation. The hybridization of safflower with its wild relatives has played an important role in the evolution of cultivars and is of particular interest with regards to their production of high quality edible oils. Original safflower varieties were all rich in linoleic acid, while varieties rich in oleic acid have risen to prominence in recent decades. The high oleic acid trait is controlled by a partially recessive allele ol at a single locus OL. The ol allele was found to be a defective microsomal oleate desaturase FAD2-1. Here we present DNA sequence data and DNA Southern blot analysis suggesting that there has been an ancient hybridization and introgression of the FAD2-1 gene into C. tinctorius from its wild relative C. palaestinus. It is from this gene that FAD2-1Δ was derived more recently. Identification and characterization of the genetic origin and diversity of FAD2-1 could aid safflower breeders in reducing population size and generations required for the development of new high oleic acid varieties by using perfect molecular marker-assisted selection.